Fiscal federalism, fiscal consolidations and cuts in central government grants : evidence from an event study - Julia Darby; Anton Muscatelli; Graeme Roy (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper we examine financial interactions between tiers of government. Whilst most existing empirical evidence has focused on the US, it is difficult to generalize conclusions obtained to countries where the position and remit of lower tiers of government is evolving or is less clear constitutionally. Applying event study methodology to a dataset covering 15 countries we examine the timing, extent and composition of fiscal changes around consolidation attempts and central government grant cuts. Highlighting the participation of central and sub-central tiers of government, our analysis also sheds light on key outcomes, including decentralized service provision and macroeconomic adjustment.
Keywords: H11; E65; E62; H77; 330; Finanzföderalismus; Finanzausgleich; Haushaltskonsolidierung; Schätzung; OECD-Staaten